Studies of Interactions of Valsartan, Glimepiride and Ciprofloxacin HCl by DSC and HPLC (Bangladesh Pharmaceutical Journal, 2018)
This article deals with the results of in vitro interactions among glimepiride, ciprofloxacin HCl and valsartan at the molar ratio of 1:1:1 by DSC and HPLC method. The DSC thermogram of the mixture (glimepiride, ciprofloxacin HCl and valsartan) showed different melting endotherm than the melting endotherm for standard valsartan, ciprofloxacin HCl and glimepiride. Since the melting endotherms of mixture and individual drugs were not identical, it demonstrated the presence of interactions among the drugs. This result was further verified by HPLC to observe their recovery range. The % recovery ranges were found as 25.33, 23.49 and 135.82% for glimepiride, ciprofloxacin HCl and valsartan, respectively. The abnormal percentage recovery range and peak areas fluctuation further indicated the interactions among glimepiride, ciprofloxacin HCl and valsartan.Bangladesh Pharmaceutical Journal 20(2): 194-199, 2017